Serum albumin-to-creatinine ratio as a novel and cost-effective biomarker for silent cerebral infarction: a retrospective cohort study - Mazıcan, Mustafa; Karluka, Ismail (Frontiers in Neurology, 2025)
Background/objectivesSilent cerebral infarction (SCI) is a common but underrecognized condition characterized by asymptomatic cerebral lesions detected via magnetic resonance imaging (MRI). While traditional vascular risk factors contribute to its pathogenesis, novel biomarkers may enhance risk stratification. The serum albumin to creatinine ratio (sACR) reflects nutritional status and renal function—two factors closely linked to vascular health. This study aimed to investigate the association between sACR and the presence of SCI, as well as its potential prognostic value for long-term outcomes.MethodsWe retrospectively analyzed 272 consecutive patients who visited the neurology outpatient clinic and underwent brain MRI for any reason, provided they met the study’s inclusion criteria. Patients with a history of cerebrovascular disease or other exclusion criteria were not included. Baseline demographic and laboratory data, including sACR, were collected. SCI was identified using standardized imaging criteria. Adverse outcomes, including cerebrovascular events and atrial fibrillation/flutter, were assessed over a median follow-up period of 37 months.ResultsPatients with SCI had significantly 24 lower sACR levels compared to those without SCI. In multivariable logistic regression analysis, each 1-point decrease in sACR was independently associated with a 1.790-fold increase in the odds of SCI (95% CI: 1.384–2.315, p < 0.001). ROC curve analysis yielded a modest discriminatory ability for sACR in predicting SCI (AUC = 0.674; cut-off: 5.13). Kaplan–Meier survival analysis showed a trend toward higher long-term outcome in the low sACR group, but this did not reach statistical significance (log-rank p = 0.088).ConclusionLower sACR levels are independently associated with the presence of SCI. While the association between sACR and long-term outcomes requires further investigation, sACR may serve as a cost-effective biomarker for assessing subclinical cerebrovascular risk. Future prospective studies are needed to validate these findings and clarify the clinical utility of sACR-guided risk stratification.